Quantifying the Sources of the Severe Haze over the Southern Hebei Using the CMAQ Model - Jing Yang; Pu Zhang; Chenchen Meng; Jie Su; Zhe Wei; Fenfen Zhang; Wei Wei; Xiujuan Zhao (The Scientific World Journal)
The Southern Hebei of China has experienced an obvious increase of the haze occurrence frequency in the recent years. It has turned out to be one of the most seriously polluted areas in China. This study is aimed at quantifying the sources of the serious haze pollution over the Southern Hebei area, using the Mesoscale Modeling System Generation 5 (MM5) and the Models-3/Community Multiscale Air Quality Model (CMAQ) modeling system. The sectoral contributions by the local and the surrounding regions to the fine particulate matter (PM2.5) concentrations in the two representative cities, Shijiazhuang and Xingtai, were analyzed by applying the method of scenario analysis. It will provide useful information to the policy making in the severe air pollution control in the Southern Hebei area.